BIOEFFICACY STUDIES OF NEW FUNGICIDE MOLECULES (RIDOMIL GOLD 68%WP) AGAINST LEAF SPOT AND FRUIT SPOT/ROT OF POMEGRANATE - A. MUTHUKUMAR; R. UDHAYAKUMAR (The Bioscan, 2015)
Leaf spot and fruit spot/rot complex in pomegranate caused by Alternaria alternata (Fr.) Keissler have emerged as a new threat in Tamil Nadu. The present investigation was undertaken at farmer’s field in Madurai during the year 2013-2014 (I and II season), to assess the field evaluation with new fungicide molecules for the management of leaf spot of pomegranate. Field evaluation for two seasons revealed that among the different treatments, spraying of Ridomil Gold 68% WP @ 3.0 ml/lit (T 5 ) recorded the lowest leaf spot (8.23 and 10.45%) and fruit rot (7.23 and 8.00%) incidence at 15 days after second spray followed by Ridomil Gold 68% WP @ 2.5 ml/lit (8.5 and 11.20 % ; 7.58 and 8.25 % ). Application of Ridomil Gold 68 %WP @ 3.0 ml/lit gave higher fruit yield (6.45 and 5.76 t/ha) while the yield of pomegranate was less in untreated control (4.25 and 3.67 t/ha). The results also showed that Ridomil Gold 68% WP @ 3.0 ml/lit and 6.0 ml/lit did not show any phytotoxicity symptoms. These fungicide molecules even at higher doses do not manifest any phytotoxicity symptoms and also exhibiting an appreciable increase in fruit yield of pomegranate.